Oasis: Pooling PCIe Devices Over CXL to Boost Utilization - Zhong, Yuhong; Berger, Daniel S.; Zardoshti, Pantea; Saurez, Enrique; Nelson, Jacob; Ports, Dan R. K.; Psistakis, Antonis; Fried, Joshua; Cidon, Asaf (The 31st Symposium on Operating Systems Principles (SOSP'25), 2025)
PCIe devices, such as NICs and SSDs, are frequently underutilized in cloud platforms. PCIe device pools, in which multiple hosts can share a set of PCIe devices, could increase PCIe device utilization and reduce their total cost of ownership. The main way to achieve PCIe device pools today is via PCIe switches, but they are expensive and inflexible. We design Oasis a system that pools PCIe devices in software over CXL memory pools. CXL memory pools are already being deployed to boost datacenter memory utilization and reduce costs. Once CXL pools are in place, they can serve as an efficient data path between hosts and PCIe devices. Oasis provides a control plane and datapath over CXL pools, mapping and routing PCIe device traffic across host boundaries. PCIe devices with different functionalities can be supported by adding an Oasis engine for each device class. We implement an Oasis network engine to demonstrate NIC pooling. Our evaluation shows that Oasis improves the NIC utilization by 2x and handles NIC failover with only a 38ms interruption.